Pengembangan Ide Bisnis Dan Peluang Usaha Kue Tart Ulang Tahun Sweet Smile Tart Brownies - Gilbert Fakambanan; Jens Batara (BADAN PENERBIT STIEPARI PRESS, 2021)
Sweet Smile Tart Brownies is a birthday cake business idea that we created with new innovation and is a business operating in the food industry. Our Sweet Smile Tart Brownies are located right on the side of the Buntao main road which will make it easier for consumers to purchase our products. It is hoped that this brownie tart business will become a unique cake shop and have a theme that is tailored to the customer's life journey. Whether it is a wedding, birthday cake and gifts for others. We will also talk to our customers and listen to what they want.